2017
DOI: 10.1002/zaac.201700088
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalytic Effect of a Series of Energetic Coordination Compounds based on Tetrazole‐1‐acetic Acid on Thermal Decomposition of HMX

Abstract: A series of energetic coordination compounds [Co(tza) 2 } n (1), [Bi(tza) 3 ] n (2), {[Cu 4 (tza) 6 (OH) 2 ]·4H 2 O} n (3), [Mn(tza) 2 ] n (4), {[Bi(tza)(C 2 O 4 )(H 2 O)]·H 2 O} n (5) and [Fe 3 O(tza) 6 (H 2 O) 3 ]NO 3 (6) based on tetrazole-1-acetic acid (Htza) were synthesized though environmentally friendly methods. The coordination compounds were characterized by elemental analyses, IR spectroscopy, single-crystal and powder X-ray diffraction (PXRD), thermogravimetric analyses (TG), and differential scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was worth mentioning that if the Fe and Bi complexes are mixed at a molar ratio of 1:2, the effect is more significant than that of the single catalyst. In 2017, K. Li et al (Qu et al, 2017) continued to use tetrazolium acetate as the ligand, and synthesized…”
Section: Monometallic Organic Frameworkbased Energetic Burning Rate C...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was worth mentioning that if the Fe and Bi complexes are mixed at a molar ratio of 1:2, the effect is more significant than that of the single catalyst. In 2017, K. Li et al (Qu et al, 2017) continued to use tetrazolium acetate as the ligand, and synthesized…”
Section: Monometallic Organic Frameworkbased Energetic Burning Rate C...mentioning
confidence: 99%
“…It was worth mentioning that if the Fe and Bi complexes are mixed at a molar ratio of 1:2, the effect is more significant than that of the single catalyst. In 2017, K. Li et al ( Qu et al, 2017 ) continued to use tetrazolium acetate as the ligand, and synthesized [Co(tza) 2 ] n ,{[Cu 4 (tza) 6 (OH) 2 ·H 2 O} n [Mn (tza) 2 ] n and {[Bi(tza) (C 2 O 4 ) (H 2 O)]·H 2 O} They then studied their influence on the thermal decomposition of HMX. Experiments showed that the synthesized complexes had obvious catalytic effect on HMX, and the Cu complex had the best catalytic effect, indicating that the catalytic effect was closely related to the oxides produced by thermal decomposition.…”
Section: Monometallic Organic Framework-based Energetic Burning Rate ...mentioning
confidence: 99%